Experimental and Modeling Studies on the Correlation Between Auto-Ignition Delays and the Methane Number of Liquefied Natural Gas (LNG) and Liquefied Biogas (LBG) - Shu, Bo; Vallabhuni, Sonal K.; Zheng, Jiaxin; Agarwal, Sumit; Fernandes, Ravi X. (Frontiers in Mechanical Engineering, 2020)
Liquefied natural gas (LNG) and liquefied biogas (LBG) as transport fuel constitute one of the pillars of the European clean fuel strategy. LNG and LBG often contain higher hydrocarbons up to C5 that lead to more complex ignition properties when utilizing them in gas engines. Therefore, it is essential to understand their combustion behavior and to quantify the abnormal combustion such as knocking propensity with correlation to the methane number (MN). Currently, there is no traceable standard to define the MN and the literature algorithms give no consistent results for the same LNG/LBG mixtures. In this study, the correlation between MN and ignition delays of several LNG/LGB mixtures containing C1 to C5 alkanes and nitrogen were investigated at temperatures between 870 and 1550 K at 10, 20, and 40 bar and with equivalence ratios of 0.4 and 1.2. Good correlations have been observed for mixtures with MN 50 to 90 at high temperatures. At intermediate temperatures, discrepancies were found between mixtures with same MN but different C1 to C3 compositions. Moreover, addition of butane and propane isomers at low vol.% showed no effect on the IDTs at intermediate temperatures.